Air pollution and subclinical interstitial lung disease: the Multi-Ethnic Study of Atherosclerosis (MESA) air–lung study. Issue 6 (7th December 2017) - Sack, Coralynn; Vedal, Sverre; Sheppard, Lianne; Raghu, Ganesh; Barr, R. Graham; Podolanczuk, Anna; Doney, Brent; Hoffman, Eric A.; Gassett, Amanda; Hinckley-Stukovsky, Karen; Williams, Kayleen; Kawut, Steve; et al.
We studied whether ambient air pollution is associated with interstitial lung abnormalities (ILAs) and high attenuation areas (HAAs), which are qualitative and quantitative measurements of subclinical interstitial lung disease (ILD) on computed tomography (CT). We performed analyses of community-based dwellers enrolled in the Multi-Ethnic Study of Atherosclerosis (MESA) study. We used cohort-specific spatio-temporal models to estimate ambient pollution (fine particulate matter (PM2.5 ), nitrogen oxides (NOx ), nitrogen dioxide (NO2 ) and ozone (O3 )) at each home. A total of 5495 participants underwent serial assessment of HAAs by cardiac CT; 2671 participants were assessed for ILAs using full lung CT at the 10-year follow-up. We used multivariable logistic regression and linear mixed models adjusted for age, sex, ethnicity, education, tobacco use, scanner technology and study site. The odds of ILAs increased 1.77-fold per 40 ppb increment in NOx (95% CI 1.06 to 2.95, p = 0.03). There was an overall trend towards an association between higher exposure to NOx and greater progression of HAAs (0.45% annual increase in HAAs per 40 ppb increment in NOx ; 95% CI −0.02 to 0.92, p = 0.06). Associations of ambient fine particulate matter (PM2.5 ), NOx and NO2 concentrations with progression of HAAs varied by race/ethnicity (p = 0.002, 0.007, 0.04, respectively, for interaction) and were strongest among non-Hispanic white people. We conclude that ambient air pollution exposures were associated with subclinical ILD. Exposure to ambient air pollution was associated with qualitative and quantitative measurements of subclinical ILD http://ow.ly/5OfU30gt2q7